Game invaders : the theory and understanding of computer games - Fencott, P. C. (Hoboken, New Jersey : IEEE Press ; Wiley, 2012)
"Introduces a practical critical method for analyzing existing games and designing future games"--
Part I. Why Do People Play Games? -- 1. You Are the One -- Tools to Think With -- Getting Started -- 2. Genre -- What Are Genres? -- What Are Genres For? -- Genre Maps -- Computer Game Genres -- A Theory of Computer Game Genres -- 3. Activity -- The Story of Activity Groups -- An Overview of Activity Profiles -- Three Driving Games -- Calculating Genres -- Tasks -- 4. Pleasure -- Aesthetics and Computer Games -- Spacewar -- Zork -- Pac-Man -- Comparative Aesthetics -- Tasks -- 5. Two Rail-Shooters -- Star Fox and Rez -- Activity Profiling and Genre Theory -- Applying Aesthetic Theory -- The Method of Game Analysis -- Tetsuya Mizuguchi, Rez, and Beyond -- 6. Why Don't People Play Games -- What Do We Mean by Games? -- Resident Evil -- Why Not Ask the Players? -- Emotional Models of Play -- Player Types -- Demographic Research -- Why Don't People Play Games? -- Conclusions -- Part II. What Is a Game? -- 7. Just an Ordinary Day -- The Glass Vial -- Unrealisms -- Perceptual Opportunities -- Sureties -- Surprises -- Attractors -- Connectors -- Rewards -- Getting It All Together in SinCity -- Perceptual Mapping in SinCity -- AS-OceanFloor -- 8. Big Bad Streets -- Driver School -- Sureties -- Surprises -- Driver and SinCity Comparisons -- 9. Time to Visit Yokosuka -- Shenmue -- Genre and Activity Profile -- Aesthetics -- Shenmue POs -- PSAS and Cut Scenes -- Interactive Storytelling? -- And On With General Aesthetics -- 10. Meaning What? -- Semiotics and Signs -- Pac-Man's Signs -- Icons, Indexes, and Symbols -- Denotation, Connotation, and Myth -- Syntagms and Paradigms -- Codes -- Making Up Pac-Man -- Filling Gaps -- 11. All Work and Play -- The Work of Meaning -- Signs of Interaction -- The Mechanics of Interaction -- The Inside-Out Code -- Where Is the Player? -- 12. Big Game Hunting -- Semiosphere -- The Code of Interaction -- The Myth of Interaction -- What Is a Game? -- How Do You Get Out of Here? -- Big Game Hunting -- Glossary -- List of Games -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Computer games; Computer games -- Design; Video games; Video games -- Design; COMPUTERS -- Programming -- Games; Computer games; Computer games -- Design; Video games; Video games -- Design; COMPUTERS -- Programming -- Games; Electronic books; Electronic books